5′‐(E)‐Vinylphosphonate: A Stable Phosphate Mimic Can Improve the RNAi Activity of siRNA–GalNAc Conjugates. (28th April 2016) - Parmar, Rubina; Willoughby, Jennifer L. S.; Liu, Jingxuan; Foster, Donald J.; Brigham, Benjamin; Theile, Christopher S.; Charisse, Klaus; Akinc, Akin; Guidry, Erin; Pei, Yi; Strapps, Walter; Cancilla, Mark; et al.
Abstract: Small interfering RNA (siRNA)‐mediated silencing requires siRNA loading into the RNA‐induced silencing complex (RISC). Presence of 5′‐phosphate (5′‐P) is reported to be critical for efficient RISC loading of the antisense strand (AS) by anchoring it to the mid‐domain of the Argonaute2 (Ago2) protein. Phosphorylation of exogenous duplex siRNAs is thought to be accomplished by cytosolic Clp1 kinase. However, although extensive chemical modifications are essential for siRNA–GalNAc conjugate activity, they can significantly impair Clp1 kinase activity. Here, we further elucidated the effect of 5′‐P on the activity of siRNA–GalNAc conjugates. Our results demonstrate that a subset of sequences benefit from the presence of exogenous 5′‐P. For those that do, incorporation of 5′‐( E )‐vinylphosphonate (5′‐VP), a metabolically stable phosphate mimic, results in up to 20‐fold improved in vitro potency and up to a threefold benefit in in vivo activity by promoting Ago2 loading and enhancing metabolic stability. Abstract : Stabilize the silence : Small interfering RNA (siRNA)‐mediated silencing requires siRNA loading into the RNA‐induced silencing complex (RISC). In contrast to natural phosphate, use of a metabolically stable phosphate mimic at the 5′‐end of an antisense strand improved the in vivo activity of modified siRNA–GalNAc conjugates in mice.